Plan de negocios para la creación de una empresa comercializadora de máquinas expendedoras de libros - López Moncayo, Galo Andrés (2021)
The general objective of this research is to formulate a business plan for the implementation of a book trading company using dispensing machines in the city of Guayaquil. To achieve the proposed purpose, the specific objectives are to diagnose the current supply of books, quantify the potential demand for reading products in the city, establish strategies for market entry and evaluate financial viability. The methodology used is descriptive, the research approach is mixed. The technique used was the survey. The population is people from the city of Guayaquil and area of influence older than 15 years. The sample amounted to 242 respondents.............